Measuring Maine’s Marine Economy - Roach, Brian; Rubin, Jonathan; Morrris, Charles (Maine Policy Review, 1999)
Even though Maine’s new license plate no longer features the lobster, the ocean remains central to Maine’s identity and to its economy. As the authors point out, Maine has more than 4,500 miles of coastline and more than 4,600 islands over one acre in size. For many who live here, their way of life is tied to the sea; for many who visit Maine, their stay is tied to the sea. Despite such prominence, it has been difficult to accurately assess the importance of Maine’s marine economy. In part, this is because there clear definition of a marine economy is lacking, as well as a method for measuring its total size. In this article, the authors present a definition of Maine’s marine economy and offer a consistent method for measuring its size relative to other sectors of the state’s economy. In doing so, they provide the first consistent measurement of Maine’s marine economy as a whole. They conclude that the state’s marine economy is not in decline, and further suggest that the potential exists for growth in key areas such as tourism and biotechnology.